Synthesis and antitumor activity of erysolin and its metabolites. Issue 4 (3rd April 2023) - Li, Bing-Long; Zhao, Shi-Zhen; Zhou, Hui; Li, Cheng-Cheng; Li, Lin-Lin; Yu, Xin-Xiang; Sun, Li-Xin
Abstract: Erysolin and its two metabolites which were found in blood, ERY-GSH and ERY-NAC, were synthesized by alkylation, amination, isothiocyanation and oxidation reactions from 1-bromo-4-chlorobutane and sodium methyl mercaptide. The reaction temperature, time, feed ratios and purification method were also optimized. The synthesis method was simple, green, safe and low-cost. Erysolin, ERY-GSH and ERY-NAC showed good antitumor activities against MCF-7, HeLa, HepG2, A549 and SW480 cells, which suggested that the antitumor mechanism of erysolin can also be clarified from its metabolites in addition to itself. Graphical Abstract: UF0001